2007
DOI: 10.1007/s11605-007-0298-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Contributing to Rapid Reoperation for Crohn’s Disease Patients Undergoing Resection and/or Strictureplasty

Abstract: Although surgically induced remission of Crohn's disease following segmental resection/strictureplasty is effective and durable, a subpopulation of patients will require rapid reoperation. We reviewed our inflammatory bowel disease center's database to identify patients who underwent multiple laparotomies. A retrospective analysis of consecutive Crohn's disease patients (1998-2004) was performed, and patients requiring repeat laparotomy were identified. Rapid reoperation was defined as repeat intestinal surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…[24][25][26] Seven of 41 (17%) patients underwent surgery in our cohort, which is slightly lower than recent studies. 27 Our analysis revealed that the presence of multiple segments alone did not correlate with failed medical therapy, 57% (4 of 7 failed medical therapy) versus 35% (8 of 23 responded to medical therapy).…”
Section: Discussioncontrasting
confidence: 68%
“…[24][25][26] Seven of 41 (17%) patients underwent surgery in our cohort, which is slightly lower than recent studies. 27 Our analysis revealed that the presence of multiple segments alone did not correlate with failed medical therapy, 57% (4 of 7 failed medical therapy) versus 35% (8 of 23 responded to medical therapy).…”
Section: Discussioncontrasting
confidence: 68%
“…Previous studies 1,6,7,9,20,21 have shown that several risk factors, such as young age, female gender, smoking history, perianal disease, extent of disease, number of sites involved, and inadequate medical therapy, may increase the risk of operative recurrence. However, these were not associated with the timing of recurrence in our study.…”
Section: Discussionmentioning
confidence: 99%
“…20 Details pertaining to the use of suppressive medication were available and comparable in both the early and late operative groups prior to the repeated operation. A further potential weakness of the study may be related to the small number of patients in the subgroups that may have precluded the derivation of a P value that was significant.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the perioperative complication rate reported by most authors spans from 0% to 57% and averages 13%. [26][27][28][29][30][31] Data for procedure-specific recurrence rates are available only for a few strictureplasty techniques. In one study, Michelassi's 32 side-to-side isoperistaltic strictureplasty was shown to have a recurrence rate of 23%.…”
Section: Discussionmentioning
confidence: 99%